New Data on Bats Hibernating in Underground Sites in Vilnius, Lithuania ... - Baranauskas, Kazimieras (Zenodo, 2006)
(Uploaded by Plazi for the Bat Literature Project) Investigations into bat diversity and abundance were carried out in Vilnius in 2005. Ten bat hibernation sites were investigated in the city where six bat species were found: Daubenton's bat (Myotis daubentonii), pond bat (Myotis dasycneme), Brandt's/whiskered bat (Myotis brandtii/mystacinus), brown long-eared bat (Plecotus auritus), barbastelle bat (Barbastella barbastellus) and northern bat (Eptesicus nilssonii). More than 820 bats roosted in Vilnius: Daubenton's bats constituted 62.5 %, barbastelle bats – 11.1% and pond bats – 10.7%. Pond bats, Daubenton's bats and barbastelle bats made up the largest known hibernating populations in south-eastern Lithuania. Brandt's/whiskered bats have been recorded in Vilnius hibernation sites for the first time. ...